(untitled) (New York, 1994)
Uses an innovative approach toward integrating biophysical and socioeconomical components into environmentally sound, sustainable forest management practices in dryland regions. Covers technical considerations in dryland forestry, agroforestry systems, rehabilitation of saline regions, investment and employment opportunities, forestry extension programs and much more
Keywords: Arid regions forestry,Arid regions agriculture,Sustainable forestry,Sustainable agriculture